2005
DOI: 10.1681/asn.2003100861
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Renal Tubular Cell Apoptosis in Focal Segmental Glomerulosclerosis

Abstract: The hypothesis that apoptosis represents a proximate mechanism by which tubule cells are damaged in FSGS was tested. Thirty kidney biopsy specimens from children with idiopathic early FSGS were studied retrospectively. Unexpected, apoptosis was evident in both proximal and distal tubule cells. There was a significant correlation between the degree of proteinuria and the number of apoptotic cells. Fas protein was detected predominantly in the tubule cells that underwent apoptosis. When compared with patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 33 publications
6
40
0
Order By: Relevance
“…A body of evidence accumulated from in vivo and in vitro protein overload systems indicates that albumin induces inflammatory and fibrogenic response in human proteinuric states. Tubule cell apoptosis induced by albumin has been proposed as a potential mechanism to explain the extensive tubular atrophy reported in chronic glomerular diseases (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A body of evidence accumulated from in vivo and in vitro protein overload systems indicates that albumin induces inflammatory and fibrogenic response in human proteinuric states. Tubule cell apoptosis induced by albumin has been proposed as a potential mechanism to explain the extensive tubular atrophy reported in chronic glomerular diseases (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was an independent predictor of ESRD. Examination of proliferation by proliferating cell nuclear antigen staining has demonstrated predominance of apoptosis over proliferation in kidney epithelial cells (18). Albumin exposure was shown to cause a mitogenic effect in wild-type opossum kidney cells via phosphatidylinositol 3-kinase, and this was inhibited by wortmannin and ⌬p85 expression (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Tubular cell apoptosis has been demonstrated during albumin treatment of cultured renal tubular cells, in proteinuric animal models and also in human patients with nephrotic syndromes. [5][6][7][8][21][22][23] Although both extrinsic and intrinsic pathways of apoptosis have been shown to contribute to tubular apoptosis during proteinuria, 5-7 recent studies have further suggested the involvement of ER stress. 8 Despite these findings, very little is known about the upstream signaling that leads to the activation of the apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…5 These in vitro observations were later shown to be relevant to renal tubular apoptosis associated with proteinuria in kidney biopsy specimens from children with focal segmental glomerulosclerosis. 6 However, in HKC-8 human proximal tubular cells, albumin-induced apoptosis was shown to be mainly mediated by the intrinsic pathway of apoptosis, characterized by Bax translocation to mitochondria and cytochrome c release from the organelles. 7 In addition, Ohse et al 8 demonstrated endoplasmic reticulum (ER) stress in albumin-treated rat kidney proximal tubular cells and proteinuric kidneys of puromycin aminonucleoside-treated rats, suggesting the involvement of ER stress in tubular apoptosis.…”
mentioning
confidence: 99%